Health Vitality of the Betawi Language in the Future in Jakarta: A Sociolinguistic Study - Sara Dwi Anjani; Iskandarsyah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study analyzes the use of the Betawi language in the Jakarta area. The aim is to find out the health vitality of the Betawi language in the future, the factors that cause the Betawi language to be endangered, and solutions to maintain the existence of the Betawi language. The theory used in this study is the Sociolinguistic theory, and the supporting theory of Cultural Sociology. The method used in this study is the mixed method, which is a step that combines two forms of research that have existed before (qualitative and quantitative). This study used observation techniques and questionnaires (questionnaire). Observation technique is a data collection technique by observation and involves recording the subject's behavior. Questionnaire technique (questionnaire) is a list of questions related to the problem being investigated. The results obtained are calculations of the current use of the Betawi language